ANALISIS ABNORMAL RETURN SAHAM, VOLUME PERDAGANGAN SAHAM, LIKUIDITAS SAHAM, DAN VARIABILITAS TINGKAT KEUNTUNGAN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT - A, Al Azhar; DP, Emrinaldi Nur; Montazeri, M Alwi (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aims to analyze abnormal stock returns, trading volume, stock liquidity,and stock gains rate variability before and after the event of stock splits (Stock Split)at the Indonesian Stock Exchange (BEI) by taking a sample of 34 companies in theobservation period 2006-2010. In this study the independent variable is theannouncement of the stock split, and the dependent variable is the abnormal stockreturns, trading volume, liquidity of the shares, and the variability of the rate of profitsaham.Metode used in this study is the event study. During the study period of 111days, this is divided into two periods during the 100-day estimation period and theevent period for 11 days including 5 days before, 1 day event, and 5 days after theevent. While test equipment is a statistical test used paired sample t-test.Pengujianthis hypothesis was tested by using SPSS version 17.0. The results showed thatthere are significant differences in abnormal stock returns before and after the stocksplit, there was no difference in trading volume before and after the stock split, thereare significant differences in stock liquidity (Bid-Ask Spread) before and after theStock Split, and no dividend rate variability differences before and after the stockSplit.Keywords : stock split, abnormal returns, trading volume, liquidity of the shares, thevariability of the rate of profit.